Oceanographic Processes of Coral Reefs: Physical and Biological Links in the Great Barrier Reef - Wolanski, Eric (CRC Press, 2009)
Demonstrating the relevance and need of science in planning the future of the Great Barrier Reef and coral reefs worldwide, Oceanographic Processes of Coral Reefs: Physical and Biological Links in the Great Barrier Reef emphasizes multi-disciplinary processes - physical and biological links - that have emerged as the dominant forces shaping and controlling the ecosystem. The book draws heavily on data from coral reefs in Australia, Indonesia, Thailand, and the Philippines.